Cancer Risks Associated With Germline PALB2 Pathogenic Variants: An International Study of 524 Families - Yang, Xin; Leslie, Goska; Doroszuk, Alicja; Schneider, Sandra; Allen, Jamie; Decker, Brennan; Dunning, Alison M; Redman, James; Scarth, James; Plaskocinska, Inga; Luccarini, Craig; Shah, Mitul; et al. (Journal of clinical oncology, 2020)
PURPOSE: To estimate age-specific relative and absolute cancer risks of breast cancer and to estimate risks of ovarian, pancreatic, male breast, prostate, and colorectal cancers associated with germline PALB2 pathogenic variants (PVs) because these risks have not been extensively characterized. METHODS: We analyzed data from 524 families with PALB2 PVs from 21 countries. Complex segregation analysis was used to estimate relative risks (RRs; relative to country-specific population incidences) and absolute risks of cancers. The models allowed for residual familial aggregation of breast and ovarian cancer and were adjusted for the family-specific ascertainment schemes. RESULTS: We found associations between PALB2 PVs and risk of female breast cancer (RR, 7.18; 95% CI, 5.82 to 8.85; P = 6.5 × 10-76), ovarian cancer (RR, 2.91; 95% CI, 1.40 to 6.04; P = 4.1 × 10-3), pancreatic cancer (RR, 2.37; 95% CI, 1.24 to 4.50; P = 8.7 × 10-3), and male breast cancer (RR, 7.34; 95% CI, 1.28 to 42.18; P = 2.6 × 10-2). There was no evidence for increased risks of prostate or colorectal cancer. The breast cancer RRs declined with age (P for trend = 2.0 × 10-3). After adjusting for family ascertainment, breast cancer risk estimates on the basis of multiple case families were similar to the estimates from families ascertained through population-based studies (P for difference = .41). On the basis of the combined data, the estimated risks to age 80 years were 53% (95% CI, 44% to 63%) for female breast cancer, 5% (95% CI, 2% to 10%) for ovarian cancer, 2%-3% (95% CI females, 1% to 4%; 95% CI males, 2% to 5%) for pancreatic cancer, and 1% (95% CI, 0.2% to 5%) for male breast cancer. CONCLUSION: These results confirm PALB2 as a major breast cancer susceptibility gene and establish substantial associations between germline PALB2 PVs and ovarian, pancreatic, and male breast cancers. These findings will facilitate incorporation of PALB2 into risk prediction models and optimize the clinical cancer risk management of PALB2 PV carriers.
Keywords: protein FANCN; zárodečné mutace; Male; nádory prsu u mužů; Genetic Predisposition to Disease; Neoplasms; Internationality; Ovarian Neoplasms; Breast Neoplasms, Male; Adult; internacionalita; Age Factors; Aged; dospělí; mužské pohlaví; senioři; nádory vaječníků; Pancreatic Neoplasms; senioři nad 80 let; Germ-Line Mutation; lidé; ženské pohlaví; Humans; nádory slinivky břišní; věkové faktory; Aged, 80 and over; Risk; nádory; Female; riziko; lidé středního věku; Fanconi Anemia Complementation Group N Protein; genetická predispozice k nemoci; Middle Aged